A Systematic Literature Review of Water-Migration-Gender Nexus Toward Integrated Governance Strategies for (Non) Migrants - Irbık, Dilare Ecenur (Frontiers in Water, 2022)
Water access and environmental migration are crucial global development issues to be examined from an interdisciplinary perspective. Although climate change and water-related dimensions of migration have been widely studied, a gendered lens on this topic is scarce in the current academic literature. To address this gap, I use insights from feminist political ecology and a water-migration-gender nexus to analyze the gender aspects in women’s experiences, challenges, and opportunities due to climate change and water stressors. After conducting a systematic literature review, 67 articles were appraised for quality and included in the synthesis to review existing policies. In the discussion section, based on these existing policies, I propose integrated governance strategies that could synergically mitigate water-related problems and (non) migration challenges with a neglected gender focus so that women and girls can prepare to be more resilient to the social, economic, and environmental changes in everyday life. This paper engages with vulnerability, tolerance, and adaptation of women and girls to socio-ecological changes around the water discourse, and it proposes a conceptual framework for the integrated governance strategies to understand better the connection between water-related security risks and development problems resulting from climate change, (non) migration, and gender.